2016
DOI: 10.1080/20445911.2016.1164710
|View full text |Cite
|
Sign up to set email alerts
|

Children view own-age faces qualitatively differently to other-age faces

Abstract: Like most own-group biases in face recognition, the own-age bias (OAB) is thought to be based either on perceptual expertise or socio-cognitive motivational mechanisms [Wolff, N., Kemter, K., Schweinberger, S. R., & Wiese, H. (2013). What drives social in-group biases in face recognition memory? ERP evidence from the own-gender bias. Social Cognitive and Affective Neuroscience. doi:10.1093/scan/nst024]. The present study employed a recognition paradigm with eye-tracking in order to assess whether participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Furthermore, Goldinger, He, and Papesh (2009) found differences in the way that own-and other-ethnicity faces are viewed, with a less effortful encoding strategy highlighted by fewer and longer fixations with more fixations to the nose for other-ethnicity faces relative to own-ethnicity faces (see also, Brielmann, Bülthoff, & Armann, 2014;Fu, Hu, Wang, Quinn, & Lee, 2012; but see, Blais, Jack, Scheepers, Fiset, & Caldara, 2008). Similarly, Hills and Willis (2016) have shown that participants focus more on the nose in other-age faces relative to own-age faces. These results indicate differential scanning for own-and other-group faces.…”
Section: Eye-tracking the Own-gender Bias In Face Recognitionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, Goldinger, He, and Papesh (2009) found differences in the way that own-and other-ethnicity faces are viewed, with a less effortful encoding strategy highlighted by fewer and longer fixations with more fixations to the nose for other-ethnicity faces relative to own-ethnicity faces (see also, Brielmann, Bülthoff, & Armann, 2014;Fu, Hu, Wang, Quinn, & Lee, 2012; but see, Blais, Jack, Scheepers, Fiset, & Caldara, 2008). Similarly, Hills and Willis (2016) have shown that participants focus more on the nose in other-age faces relative to own-age faces. These results indicate differential scanning for own-and other-group faces.…”
Section: Eye-tracking the Own-gender Bias In Face Recognitionmentioning
confidence: 89%
“…Inverted faces are typically processed in an inexpert manner (Kanwisher, Tong, & Nakayama, 1998;McKone & Yovel, 2009;Tanaka & Farah, 1993). Reduced expert processing (and a smaller face-inversion effect) has been revealed for faces of other groups relative to own group faces (Hills & Willis, 2016;Hugenberg & Corneille, 2008;Michel, Rossion, Han, Chung, & Caldara, 2006;Rhodes, Brake, Taylor, & Tan, 1989). The perceptual expertise account is typically contrasted with the socio-cognitive motivational accounts.…”
Section: Eye-tracking the Own-gender Bias In Face Recognitionmentioning
confidence: 99%
“…The images of faces used in this study was selected from the database held by Stirling University ( PICS, 2014 ): As in the original CFMT, six identities were used as targets for the upright and a different six identities (counterbalanced across participants) were used as targets in the inverted versions. All faces used within the study were of male individuals aged between 18 and 40 years (mean age 25 years) in order to match the age of the participants (note identical age range to participants) in order to prevent any effects of the own-age bias ( Anastasi and Rhodes, 2005 ; Hills and Willis, 2016 ). The images were matched for lighting, expression, and pose.…”
Section: Methodsmentioning
confidence: 99%
“…This bias is dependent upon differential experience with face age (31,32), is reduced by visual exposure training of other-aged faces (33), and has been reliably observed in both tasks of face recognition memory (11) and FER (10,34). As is true of many indicators of perceptual expertise, the OAB is also reflected in differential patterns of visual attention to own-age faces (35)(36)(37)(38)(39) and the recruitment of specialized cortical networks when processing own-age faces (36,40).…”
Section: Introductionmentioning
confidence: 97%